Altered Interferon Responses in Tuberculosis Patients with Type II Diabetes: Implications for Increased Disease Susceptibility - Nofri Rahmadika; Jackie M Cliff; Ji Sook Lee (Journal of Global Antimicrobial Resistance)
BACKGROUND: Individuals with type 2 diabetes are three times more likely to develop active tuberculosis (TB) after infection compared to those without diabetes. The mechanisms behind this increased risk remain unclear but may involve abnormal immune responses, including enhanced pro-inflammatory activity and altered cell phenotypes, particularly involving type-1 and type-2 interferon responses. METHOD: This study used flow cytometry and ELISA to assess type-1 and type-2 interferon production in peripheral blood mononuclear cells (PBMCs) from healthy BCG-vaccinated donors exposed to live Mycobacterium bovis (BCG). The expression of six type-1 interferon-inducible genes was evaluated in PBMC and whole blood cultures using quantitative real-time RT-PCR. Additionally, plasma IFNα/γ levels in tuberculosis patients with and without type II diabetes (n = 120) were measured.Results revealed that IFN-α was undetectable in PBMCs cultured with BCG, although six IFN-α-responsive genes were notably upregulated. IFN-γ levels were significantly elevated in TB-only and TB-pre-DM patients, but not in those with both TB and diabetes. Plasma IFN-α levels remained consistently low across all patient groups, with no significant differences detected.These findings suggest that IFN-γ responses vary among TB patients depending on their diabetes status. IFN-α is not significantly upregulated in response to BCG stimulation in PBMCs. This highlights the complexity of the immune response in TB patients with type II diabetes and suggests a potential role of interferon pathways in their increased susceptibility to TB.